The Influence of Auditor, Financial Ratios, And Corporate Governance on Fraudulent Financial - Wulan Dwi Nurcahyaningsih; Purnama Siddi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Financial reports are reports that show information about financial data and company operational activities to be given to parties who have an interest in the company (stakeholders). Companies publish financial reports aimed at displaying the actual condition or state of the company. This study aims to examine and analyze the influence of auditors, financial ratios and corporate governance on fraudulent financial reporting of coal mining companies on the IDX for the 2016-2019 period. The population in this study are coal mining companies listed on the IDX for the 2016-2019 period. In taking the sample using purposive sampling technique, in order to obtain a sample of 8 coal mining companies. The data was collected using documentation techniques obtained from the official website www.idx.co.id. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the activity ratio, profitability ratio has an effect on fraudulent financial reporting, while the auditor, liquidity ratio, leverage ratio, gross profit margin, and corporate governance have no effect on fraudulent financial reporting.